Rubber composition for fenders and fenders using the same
Patent Information
- Application Number
- JP2025059272
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166384000003 
Figure 2026166384000004 
Figure 2026166384000005
Abstract
Description
[Technical Field]
[0001] This invention relates to a rubber composition for fenders and a fender using the same. [Background technology]
[0002] Traditionally, rubber fenders have been used to absorb the energy generated when ships dock or approach a berth. Various rubber compositions have been proposed for use in fenders.
[0003] Patent Document 1 contains rubber and carbon black, wherein the amount of carbon black [g] per 100g of rubber is 65g or more and 80g or less, and the nitrogen adsorption specific surface area of the carbon black [m²] 2 The total surface area of the carbon black [m²] is expressed as the product of [g] and the amount [g]. 2 ] is 1500m 2 More than 5000m 2 The following rubber composition for fenders is disclosed.
[0004] Patent Document 2 describes rubber, (A) nitrogen adsorption specific surface area S A 70m 2 Carbon black of 1g or more, and (B) Nitrogen adsorption specific surface area S A 70m 2 A rubber composition for fenders is disclosed, which contains less than 1g of carbon black, wherein the proportion of carbon black (A) per 100 parts by mass of the total amount of rubber is 60 parts by mass or less, and the total proportion of carbon black (A) and (B) is 65 parts by mass or more and 80 parts by mass or less.
[0005] Patent Document 3 discloses a rubber composition for fenders comprising rubber, carbon black, and a crosslinking component for crosslinking the rubber, wherein the maximum value of the loss loss tangent of the crosslinked material in the temperature range of -70°C to +70°C, as determined by the measurement method specified in Japanese Industrial Standard JIS K6394:2007, is 0.48 or more.
[0006] Patent Document 4 discloses a rubber composition for fenders, which contains a base rubber including natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the amount of sulfur is 0.8 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2022-76692 [Patent Document 2] Japanese Patent Publication No. 2022-25537 [Patent Document 3] Japanese Patent Publication No. 2022-145069 [Patent Document 4] Japanese Patent Publication No. 2025-20954 [Overview of the project] [Problems that the invention aims to solve]
[0008] Patent documents 1 to 3 propose rubber compositions for fenders that have good rubber properties and whose arch-shaped fender legs are prone to buckling deformation when docking with ships, etc., and which can be manufactured more cheaply by adding 65 to 80 parts by mass of carbon black per 100 parts by mass of total rubber. However, rubber compositions with a high amount of carbon black such as these may have a shortened vulcanization induction time and may experience scorching during molding, resulting in poor processability.
[0009] One way to lengthen the vulcanization induction time is to lower the molding temperature, but this has the problem of increasing the crosslinking time. Another method to lengthen the vulcanization induction time is to incorporate crosslinking retarders such as N-(cyclohexylthio)phthalimide, but this has the problem of reducing the reaction force of the fender, making it impossible to obtain the desired reaction force.
[0010] One way to obtain high-reaction fenders is to reduce the amount of plasticizers such as oil, but reducing the amount of plasticizer shortens the vulcanization induction time of the rubber composition, worsening moldability. In addition, the elongation of the crosslinked components of the rubber composition may decrease, potentially resulting in a failure to obtain the rubber properties required for fenders.
[0011] The present invention has been made in view of the above circumstances, and aims to provide a rubber composition for fenders that increases the vulcanization induction time, improves processing stability, and does not reduce the reaction force of the resulting fender. A further object of the present invention is to provide a fender using this rubber composition for fenders. [Means for solving the problem]
[0012] The rubber composition for fenders of the present invention, which has been able to solve the aforementioned problems, contains a base rubber containing natural rubber, carbon black, a crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and a crosslinking accelerator, characterized in that the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is 0.1 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
[0013] As a result of intensive studies to solve the above-mentioned problems, the present inventors have found that by blending both 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane and a crosslinking accelerator into a rubber composition for fenders, and setting the blending amount of 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane to 0.1 parts by mass or more and less than 1.0 parts by mass relative to 100 parts by mass of the base rubber, the vulcanization induction time is prolonged, the processing stability is improved, and the reaction force of the obtained fender does not decrease, thereby completing the present invention.
[0014] Incidentally, the present inventor has filed an application (Japanese Patent Application No. 2023-124604) for an invention relating to a rubber composition for fenders in which 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane is blended in an amount of 1.0 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the base rubber (the aforementioned Patent Document 4). However, from the viewpoint of cost, it is preferable that the amount of compounding chemicals such as 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane is as small as possible. The present inventor has found that even when 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane is blended in an amount of less than 1.0 parts by mass, the vulcanization induction time of the rubber composition can be prolonged compared to a system not blended with 1,6-bis(N,N-dibenzyldithiocarbamoyl)hexane, and a useful rubber composition that does not reduce the reaction force of the fender can be obtained.
Effects of the Invention
[0015] According to the present invention, it is possible to provide a rubber composition for fenders that has a prolonged vulcanization induction time, improved processing stability, and does not reduce the reaction force of the obtained fender, and a fender using the same.
Brief Description of the Drawings
[0016] [Figure 1] It is an end view showing the external appearance of a lambda-type reduced fender test specimen produced for measuring the compressibility-reaction force characteristics in each example of the present invention. [Figure 2] It is a graph showing the compressibility-reaction force characteristics of Fender No. 1. [Figure 3]This graph shows the compressibility-reaction force characteristics of fender No. 2. [Figure 4] This graph shows the compressibility-reaction force characteristics of fender No. 3. [Figure 5] This graph shows the compressibility-reaction force characteristics of fender No. 4. [Figure 6] This graph shows the compressibility-reaction force characteristics of fender No. 5. [Figure 7] This graph shows the compressibility-reaction force characteristics of fender No. 6. [Figure 8] This graph shows the compressibility-reaction force characteristics of fender No. 7. [Figure 9] This graph shows the compressibility-reaction force characteristics of fender No. 8. [Modes for carrying out the invention]
[0017] <Rubber composition for fenders> The rubber composition for fenders of the present invention contains a base rubber including natural rubber, carbon black, a crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and a crosslinking accelerator, characterized in that the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is 0.1 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
[0018] The raw materials for the rubber composition for fenders of the present invention will be described below.
[0019] (Base rubber) The base rubber contained in the rubber composition for fenders of the present invention mainly consists of natural rubber (NR). This is because including natural rubber as the main component of the base rubber makes it easier to obtain the rubber properties required for fenders (for example, good compressibility-reaction force characteristics).
[0020] Natural rubber is produced by damaging plants that produce natural rubber latex (emulsion), collecting the latex, and then coagulating the rubber components contained in the latex. It contains naturally derived cis-1,4-polyisoprene.
[0021] Examples of plants that produce the aforementioned natural rubber latex include the Para rubber tree and the Cearan rubber tree of the Euphorbiaceae family, the Indian rubber tree, the Panagane rubber tree, and the Lagos rubber tree of the Moraceae family, the arabic rubber tree and the Tragacanth rubber tree of the Fabaceae family, the veronica tree, the Zanzibar fig tree, the Funthumia elastica, and the Urseola of the Apocynaceae family, the guayure rubber tree and the rubber dandelion of the Asteraceae family, the gatapacha tree, the Barata rubber tree and the sapodilla of the Sapotaceae family, the large-flowered morning glory of the Milkweed family, and the Eucommia ulmoides of the Eucommia family.
[0022] The aforementioned natural rubbers include CV grades, in which a viscosity constant agent or the like is added to the raw material latex to stabilize the rubber viscosity, and non-CV grades, in which the rubber viscosity is not stabilized. These may be used individually or in combination of two or more types. Among these, CV grades, which have particularly stable viscosity, are preferred. The aforementioned natural rubber may be either SMR (Standard Malaysian Rubber) or SVR (Standard Vietnamese Rubber).
[0023] Examples of natural rubber included in the base rubber include various grades of natural rubber such as TSR (e.g., TSR20) and RSS (e.g., RSS3), as well as various types of deproteinized natural rubber. TSR (Technically Specified Rubber) is natural rubber obtained by crushing rubber latex that has naturally solidified in a collection cup, washing it, molding it into blocks, and then performing quality inspections. RSS (Ribbed Smoked Sheet) is natural rubber obtained by solidifying latex extracted from rubber trees, pressing it into a sheet using a roll, and then drying it with smoke. These natural rubbers may be used individually or in combination of two or more types.
[0024] The natural rubber content in the base rubber is preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more. This is because a natural rubber content of 50% by mass or more makes it easier to obtain the rubber properties required for fenders (for example, good compressibility-reaction force characteristics). The natural rubber content in the base rubber may be 100% by mass, but from the viewpoint of improving processability, it is preferably 95% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.
[0025] The rubber base material contained in the rubber composition for fenders of the present invention preferably further contains styrene-butadiene rubber (SBR) in addition to the natural rubber. This is because the inclusion of styrene-butadiene rubber in the base material improves processability.
[0026] The styrene-butadiene rubber is a synthetic rubber obtained by copolymerizing styrene and butadiene. There are two types of styrene-butadiene rubber depending on the polymerization method: emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR). In the present invention, it is preferable to use emulsion-polymerized styrene-butadiene rubber (E-SBR). Styrene-butadiene rubber may be used alone or in combination of two or more types. The styrene-butadiene rubber can be an oil-expanded type in which an extensible oil is added to adjust its flexibility, or a non-oil-expanded type in which no extensible oil is added. In the present invention, either type can be used.
[0027] Specific examples of the aforementioned styrene-butadiene rubber include commercially available products such as the non-oil-expandable SBR1500 and SBR1502, and the oil-expandable SBR1723, manufactured by JSR Corporation.
[0028] The content of styrene-butadiene rubber in the base rubber is preferably 5% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. This is because if the content of styrene-butadiene rubber is within the above range, good processability can be obtained without impairing the rubber properties of natural rubber.
[0029] From the above viewpoint, the mass ratio of natural rubber to styrene-butadiene rubber in the base rubber (natural rubber / styrene-butadiene rubber) is preferably 1.0 or higher, more preferably 1.2 or higher, even more preferably 1.5 or higher, preferably 19.0 or lower, more preferably 6.0 or lower, and even more preferably 4.0 or lower.
[0030] The base rubber may also contain other synthetic rubbers in addition to the natural rubber and styrene-butadiene rubber.
[0031] Examples of the other synthetic rubbers mentioned above include polybutadiene rubber (BR), polyisoprene rubber (IR), chloroprene rubber (CR), butyl rubber (IIR), acrylonitrile butadiene rubber (NBR), and ethylene-propylene-diene rubber (EPDM). These other synthetic rubbers may be used individually or in combination of two or more types. It should be noted that the other synthetic rubbers include oil-expanded types with added stretching oil to adjust flexibility, and non-oil-expanded types without added stretching oil; however, both types can be used in this invention.
[0032] The total content of natural rubber and styrene-butadiene rubber in the base rubber of the fender rubber composition of the present invention is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. This is because a total content of natural rubber and styrene-butadiene rubber of 80% by mass or more results in better rubber properties (e.g., good compressibility-reaction force characteristics) and processability required for fender materials. From this viewpoint, it is most preferable that the base rubber of the fender rubber composition of the present invention consists only of natural rubber and styrene-butadiene rubber.
[0033] In this invention, when using an oil-expandable type of styrene-butadiene rubber or other synthetic rubber, the content of the oil-expandable type shall be the content of the rubber itself as an active ingredient contained therein.
[0034] The base rubber contained in the rubber composition for fenders of the present invention preferably exhibits a solid state at 25°C. In this respect, the base rubber is distinguished from liquid rubber that exhibits a liquid state at 25°C and can be used as a plasticizer.
[0035] (Carbon Black) The rubber composition for fenders of the present invention contains carbon black. The type of carbon black is not particularly limited, and various types of carbon black that can function as a rubber filler (filler, reinforcing agent) can be used. Examples of the carbon black include furnace carbon blacks such as SAF (Super Abrasion Furnace Black), ISAF (Intermediate Super Abrasion Furnace Black), IISAF (Intermediate ISAF), HAF (High Abrasion Furnace Black), MAF (Medium Abrasion Furnace Black), FEF (Fast Extruding Furnace Black), SRF (Semi-Reinforcing Furnace Black), GPF (General Purpose Furnace Black), FF (Fine Furnace Black), and CF (Conductive Furnace Black); thermal carbon blacks such as FT (Fine Thermal Black) and MT (Medium Thermal Black); channel carbon blacks such as EPC (Easy Processing Channel Black) and MPC (Medium Processing Channel Black); acetylene black; and Ketjen black. The carbon black may be used individually or in combination of two or more types.
[0036] As the carbon black, it is particularly preferable to use furnace carbon blacks such as SAF, ISAF, HAF, MAF, FEF, GPF, and SRF. These furnace carbon blacks may be used alone, or two or more thereof may be used in combination.
[0037] Specific examples of the carbon black include commercially available products such as the SEAST (registered trademark) series manufactured by Tokai Carbon Co., Ltd..
[0038] The blending amount of the carbon black is preferably 60 parts by mass or more, more preferably 65 parts by mass or more, further preferably 70 parts by mass or more, and is preferably 90 parts by mass or less, more preferably 88 parts by mass or less, further preferably 85 parts by mass or less, relative to 100 parts by mass of the base rubber. When the blending amount of the carbon black is 60 parts by mass or more relative to 100 parts by mass of the base rubber, the reinforcing property for the base rubber becomes better, and when it is 90 parts by mass or less, the hardness and buckling deformation of the fender become more appropriate.
[0039] In the present invention, it is preferable to use a carbon black having a strong reinforcing property for the base rubber and a large nitrogen adsorption specific surface area in combination with a carbon black having a weak reinforcing property for the base rubber and a small nitrogen adsorption specific surface area. This is because the combined use of these carbon blacks makes it easy to adjust the hardness of the fender to a more appropriate range while favorably maintaining the reinforcing property for the base rubber.
[0040] The nitrogen adsorption specific surface area of the carbon black having a large nitrogen adsorption specific surface area is 60 m 2 / g or more, preferably 65 m 2 / g or more, more preferably 70 m 2 / g or more, further preferably. The nitrogen adsorption specific surface area of the carbon black having a large nitrogen adsorption specific surface area is not particularly limited, but is 120 m 2 / g or less, preferably 100 m 2 / g or less, more preferably.
[0041] The nitrogen adsorption specific surface area of the carbon black with a small nitrogen adsorption specific surface area is 50 m². 2 Preferably less than / g, 45m 2 More preferably less than / g, 40m 2 A value of less than / g is even more preferable. Furthermore, the nitrogen adsorption specific surface area of the carbon black with a small nitrogen adsorption specific surface area is not particularly limited, but is 10m 2 Preferably 20m / g or more. 2 A value of / g or higher is more preferable.
[0042] The nitrogen adsorption specific surface area can be measured, for example, in accordance with JIS K6217-2:2001.
[0043] The mass ratio of carbon black with a large nitrogen adsorption specific surface area to carbon black with a small nitrogen adsorption specific surface area (carbon black with a large nitrogen adsorption specific surface area / carbon black with a small nitrogen adsorption specific surface area) is preferably 1.0 or higher, more preferably 1.5 or higher, even more preferably 2.0 or higher, preferably 5.0 or lower, more preferably 4.5 or lower, and even more preferably 4.0 or lower.
[0044] (Crosslinking agent) The rubber fender composition of the present invention further contains a crosslinking agent.
[0045] It is preferable to use a sulfur-based crosslinking agent as the crosslinking agent. Examples of sulfur-based crosslinking agents include powdered sulfur, oil-treated powdered sulfur, precipitated sulfur, colloidal sulfur, and dispersible sulfur. These sulfur-based crosslinking agents may be used individually or in combination of two or more.
[0046] Specific examples of the aforementioned crosslinking agent include commercially available products such as 5% oil-treated sulfur powder manufactured by Tsurumi Chemical Industries Co., Ltd.
[0047] The amount of the crosslinking agent is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, even more preferably 1.0 part by mass or more, preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber. This is because if the amount of the crosslinking agent is within the above range, it is easier to obtain a rubber crosslinked material suitable for use as a fender. When using, for example, oil-treated powdered sulfur or dispersible sulfur as the sulfur, the amount of the crosslinking agent refers to the amount of sulfur itself as an active ingredient contained in each.
[0048] (1,6-Bis(N,N-Dibenzylthiocarbamoyldithio)hexane) The fender rubber composition of the present invention further contains 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
[0049] The aforementioned 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane has the following structure.
[0050] [ka]
[0051] Specific examples of the aforementioned 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane include commercially available products such as Vulcuren® manufactured by LANXESS.
[0052] The amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, and even more preferably 0.2 parts by mass or more, per 100 parts by mass of the base rubber. This is because the blending effect of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is enhanced when the blending amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.1 parts by mass or more. Furthermore, from the viewpoint of cost reduction, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably less than 1.0 part by mass, and more preferably 0.95 parts by mass or less, per 100 parts by mass of the base rubber.
[0053] (Crosslinking promoter) The rubber composition for fenders of the present invention further contains a crosslinking accelerator.
[0054] Examples of the aforementioned crosslinking accelerators include thiazole-based crosslinking accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide; dithiocarbamate-based accelerators such as zinc dimethyldithiocarbamate; thiuram-based crosslinking accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based crosslinking accelerators such as N-cyclohexyl-2-benzothiadylsulfenamide (CBS), N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-oxyethylene-2-benzothiazolesulfenamide, and N,N′-diisopropyl-2-benzothiazolesulfenamide; and guanidine-based crosslinking accelerators such as diphenylguanidine, diortotrilguanidine, and orthotrilbiguanidine. Commercially available products from companies such as Sumitomo Chemical Co., Ltd. and Ouchi Shinko Chemical Industry Co., Ltd. can be used. These may be used individually or in combination of two or more types.
[0055] Specific examples of the aforementioned crosslinking accelerator include, for example, the Noxellar® series (e.g., Noxellar NS) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0056] The amount of the crosslinking accelerator is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, even more preferably 1.0 part by mass or more, preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber. This is because the effects of the present invention are more easily obtained when the amount of the crosslinking accelerator is within the above range.
[0057] The total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 0.6 parts by mass or more, more preferably 1.0 part by mass or more, even more preferably 1.5 parts by mass or more, preferably less than 4.0 parts by mass, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less, per 100 parts by mass of the base rubber. This is because the effects of the present invention are more easily obtained when the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is within the above range.
[0058] Furthermore, the inventors have found that in an embodiment where the amount of crosslinking accelerator is less than or equal to the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane (hereinafter sometimes referred to as "Embodiment 1"), the elongation of the crosslinked product of the fender rubber composition is further increased, and in an embodiment where the amount of crosslinking accelerator is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane (hereinafter sometimes referred to as "Embodiment 2"), the crosslinking rate of the fender rubber composition is further increased. Embodiments 1 and 2 will be described below.
[0059] [Aspect 1] Embodiment 1 is an embodiment in which the amount of crosslinking accelerator blended with 100 parts by mass of base rubber is less than or equal to the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended with 100 parts by mass of base rubber.
[0060] This embodiment 1, compared to the case where only a crosslinking accelerator is included without 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, allows for a longer vulcanization induction time of the fender rubber composition, without reducing the reaction force of the fender, and also increases the elongation of the crosslinked material of the fender rubber composition. Since the crosslinked material of rubber compositions used in fenders is often required to have an elongation of 350% or more, being able to increase the elongation without reducing the reaction force increases the degree of freedom in compound design, making it easier to obtain fenders with high reaction force.
[0061] From the viewpoint of making it easier to obtain the effects of the above embodiment 1, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, and even more preferably 0.7 parts by mass or more, per 100 parts by mass of the base rubber. Also, from the viewpoint of cost reduction, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably less than 1.0 part by mass, and more preferably 0.95 parts by mass or less, per 100 parts by mass of the base rubber.
[0062] The amount of the crosslinking accelerator is not particularly limited as long as it is less than or equal to the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, but from the above viewpoint, it is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, even more preferably 0.7 parts by mass or more, preferably less than 1.0 part by mass, and more preferably 0.95 parts by mass or less, per 100 parts by mass of the base rubber.
[0063] From a similar viewpoint, the difference between the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and the amount of the crosslinking accelerator (1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane-crosslinking accelerator) is preferably 0 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.2 parts by mass or more, preferably less than 0.5 parts by mass, and more preferably 0.4 parts by mass or less, per 100 parts by mass of the base rubber.
[0064] From a similar viewpoint, the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 1.0 part by mass or more, more preferably 1.2 parts by mass or more, even more preferably 1.5 parts by mass or more, preferably less than 2.0 parts by mass, and more preferably 1.9 parts by mass or less, per 100 parts by mass of the base rubber.
[0065] [Aspect 2] Embodiment 2 is an embodiment in which the amount of crosslinking accelerator is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
[0066] This embodiment 2, compared to the case in which only a crosslinking accelerator is added without 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, allows for a longer vulcanization induction time of the fender rubber composition, without reducing the reaction force of the fender, and also shortens Δtc(80), which is an indicator of the crosslinking rate (i.e., increases the crosslinking rate). Here, Δtc(80) is the difference (tc(90)-tc(10)) between the 90% vulcanization time tc(90), which is considered the optimal vulcanization point, and the 10% vulcanization time tc(10), which is considered the vulcanization start point (vulcanization induction time). Solid-type fenders are lumps of rubber and some are very large. Crosslinking large fenders often takes a long time, so if the crosslinking rate can be increased, a reduction in crosslinking time can be expected.
[0067] From the viewpoint of making it easier to obtain the effects of the above embodiment 2, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, and even more preferably 0.2 parts by mass or more, per 100 parts by mass of the base rubber. Also, from the viewpoint of cost reduction, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably less than 1.0 part by mass, and more preferably 0.95 parts by mass or less, per 100 parts by mass of the base rubber. Furthermore, from the viewpoint of increasing tear strength, the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is even more preferably 0.5 parts by mass or less, and most preferably less than 0.5 parts by mass, per 100 parts by mass of the base rubber.
[0068] The amount of the crosslinking accelerator is not particularly limited as long as it is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, but from the above viewpoint, it is preferably 0.5 parts by mass or more, more preferably 1.0 part by mass or more, even more preferably 1.5 parts by mass or more, preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber.
[0069] From a similar viewpoint, the difference between the amount of the crosslinking accelerator and the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane (crosslinking accelerator - 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane) is preferably more than 0 parts by mass, more preferably 0.5 parts by mass or more, even more preferably 1.0 part by mass or more, preferably 2.9 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber.
[0070] From a similar viewpoint, the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is preferably 0.6 parts by mass or more, more preferably 1.0 part by mass or more, even more preferably 1.5 parts by mass or more, preferably less than 4.0 parts by mass, more preferably 3.5 parts by mass or less, and even more preferably 3.0 parts by mass or less, per 100 parts by mass of the base rubber.
[0071] (Other ingredients) In addition to the above-mentioned components, the rubber composition for fenders of the present invention may further contain various additives that can be used in rubber compositions for fenders, such as crosslinking aids, crosslinking retarders, plasticizers, antioxidants, waxes, colorants, tackifiers, and other fillers other than carbon black, selected as appropriate within the scope that does not impair the objectives of the present invention.
[0072] [Crosslinking agent] Examples of the aforementioned crosslinking aids include metal compounds such as zinc oxide, and fatty acids such as stearic acid, oleic acid, and cottonseed fatty acid. These crosslinking aids may be used individually or in combination of two or more.
[0073] Specific examples of the aforementioned crosslinking aids include commercially available products such as two types of zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. and Tsubaki manufactured by NOF Corporation.
[0074] The amount of the crosslinking aid is preferably 4.0 parts by mass or more, more preferably 4.5 parts by mass or more, even more preferably 5.0 parts by mass or more, preferably 8.0 parts by mass or less, more preferably 7.5 parts by mass or less, and even more preferably 7.0 parts by mass or less, per 100 parts by mass of the base rubber. If the amount of the crosslinking aid is within the above range, the crosslinking rate can be controlled more appropriately.
[0075] Furthermore, it is preferable to use a metal compound and a fatty acid in combination as crosslinking aids. In this case, the mass ratio of the metal compound to the fatty acid (metal compound / fatty acid) is preferably 1.2 or higher, more preferably 1.5 or higher, preferably 2.5 or lower, and more preferably 2.3 or lower. If the mass ratio of the metal compound to the fatty acid is within the above range, the crosslinking rate can be controlled more appropriately.
[0076] [Crosslinking retarder] Examples of the crosslinking retarders include thioimide derivatives such as N-(cyclohexylthio)phthalimide, N-(2-ethylhexylthio)phthalimide, N-(cyclohexylthio)maleimide, and N-(4-t-butylphenylthio)succinimide; aromatic monocarboxylic acids such as benzoic acid and salicylic acid; amide derivatives such as N-isopropylthio-N-cyclohexyl-benzothiadyl-2-sulfonamide, N-cyclohexyl-N-trichloromethylthio-benzyl-2-sulfonamide, and N-phenyl-N-trichloromethylthiobenzenesulfonamide; and aromatic dicarboxylic acids or their acid anhydrides such as orthophthalic acid, phthalic anhydride, isophthalic acid, and terephthalic acid. These crosslinking retarders may be used alone or in combination of two or more.
[0077] Specific examples of the aforementioned crosslinking retarder include commercially available products such as Retarder CTP manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0078] When the crosslinking retarder is incorporated, the amount is preferably 0.01 or more, more preferably 0.05 or more, 0.5 or less, and more preferably 0.3 or less, per 100 parts by mass of the base rubber. If the amount of the crosslinking retarder is within the above range, the vulcanization induction time can be extended and the crosslinking speed can be controlled more appropriately. However, if a crosslinking retarder is incorporated to extend the vulcanization induction time, the reaction force of the fender decreases. Therefore, from the viewpoint of more easily obtaining the effects of the present invention, it is preferable that the rubber composition for fenders of the present invention does not contain a crosslinking retarder.
[0079] [Plasticizer] Examples of the aforementioned plasticizers include oil and liquid rubber. These plasticizers may be used individually or in combination of two or more. In this invention, liquid rubber refers to rubber that is liquid at 25°C and is not included in the base rubber described above.
[0080] Specific examples of the aforementioned oils include commercially available products such as Process NC300SN manufactured by Sunyu Industrial Co., Ltd., and Diana® Process Oil PW, NH, NP, NS, NR, NM, AC, and AH manufactured by Idemitsu Kosan Co., Ltd.
[0081] Examples of the liquid rubber include liquid polybutadiene rubber, liquid polyisoprene rubber, and liquid polystyrene-butadiene rubber. Specific examples include commercially available products such as Kuraray's Kuraprene® LBR series, LIR series, and L-SBR series.
[0082] The amount of plasticizer added is preferably 5.0 parts by mass or more, more preferably 8.0 parts by mass or more, even more preferably 10.0 parts by mass or more, preferably 35.0 parts by mass or less, more preferably 30.0 parts by mass or less, and even more preferably 25.0 parts by mass or less, per 100 parts by mass of the base rubber. This is because if the amount of plasticizer added is within the above range, the hardness of the fender can be adjusted to a more appropriate range.
[0083] [Anti-aging agent] As the aforementioned anti-aging agent, various anti-aging agents classified by their main function, such as weather-resistant anti-aging agents and heat-resistant anti-aging agents, can be used. Examples of such anti-aging agents include amine-ketone systems, aromatic secondary amine systems, (mono, bis, or poly)phenol systems, benzimidazole systems, and dithiocarbamate systems. These anti-aging agents may be used alone or in combination of two or more.
[0084] Specific examples of the aforementioned anti-aging agents include commercially available products such as the Nocrack® series manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0085] As the aforementioned anti-aging agent, aromatic secondary amine-based anti-aging agents are preferred due to their excellent effectiveness in preventing solar cracking, ozone cracking, and flexing cracking, and N-phenyl-N′-(1,3-dimethylbutyl)-p-phenylenediamine is more preferred.
[0086] The amount of antioxidant added is preferably 2.0 parts by mass or more, more preferably 2.5 parts by mass or more, even more preferably 3.0 parts by mass or more, preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 6.0 parts by mass or less, per 100 parts by mass of the base rubber. This is because good anti-aging properties are obtained when the amount of antioxidant added is within the above range.
[0087] [wax] Examples of the aforementioned waxes include natural waxes such as animal waxes, plant waxes, mineral waxes, and petroleum waxes, as well as synthetic waxes.
[0088] Specific examples of the aforementioned waxes include commercially available products such as the Ozoace® series manufactured by Nippon Seiro Co., Ltd. and the Sunnock® series manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0089] The amount of wax added is preferably 1.0 part by mass or more, more preferably 1.5 parts by mass or more, even more preferably 2.0 parts by mass or more, preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, per 100 parts by mass of the base rubber. This is because if the amount of wax added is within the above range, the ozone resistance will be good.
[0090] The rubber composition for fenders of the present invention can be prepared, for example, by kneading a base rubber, carbon black, a crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, a crosslinking accelerator, and other components to be added as needed. The kneading method is not particularly limited and can be carried out using known kneading machines such as a closed-type kneader, kneading rolls, Banbury mixer, or kneader. It is preferable to knead each of the above components except for the crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and the crosslinking accelerator, and then add these components and knead further.
[0091] The rubber composition for fenders of the present invention can be suitably used, for example, in fenders installed on quays and the like to protect ships and quays from impacts and friction that occur when ships dock or moor.
[0092] <Fender> The present invention includes a fender using the rubber composition for fenders of the present invention, specifically a fender having a head portion having a contact surface for contact with ships and the like, and a support leg portion that supports the head portion, wherein at least the support leg portion contains a crosslinked product of the rubber composition for fenders of the present invention.
[0093] The fenders of the present invention can be manufactured by conventional methods for manufacturing fenders. For example, using the rubber composition for fenders of the present invention, fenders can be manufactured by combining any process such as molding, sheet molding, assembly, and crosslinking, depending on the size and shape of the fenders to be manufactured.
[0094] The vulcanization induction time tc(10) at 140°C for the rubber composition for fenders of the present invention is preferably 10 minutes or more, more preferably 12 minutes or more, even more preferably 14 minutes or more, preferably 30 minutes or less, more preferably 25 minutes or less, and even more preferably 20 minutes or less. This is because if the vulcanization induction time is within the above range, scorching is less likely to occur during molding, and molding can be performed without increasing the vulcanization molding time. The vulcanization flow time tc(10) of the rubber composition is measured by the method described later.
[0095] The crosslinking temperature for the rubber composition for fenders of the present invention is not particularly limited, but is preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, preferably 180°C or lower, more preferably 170°C or lower, and even more preferably 160°C or lower.
[0096] The crosslinking time for crosslinking the rubber composition for fenders of the present invention is not particularly limited, but is preferably 60 minutes or more, more preferably 90 minutes or more, even more preferably 120 minutes or more, preferably 1500 minutes or less, more preferably 1200 minutes or less, and even more preferably 600 minutes or less.
[0097] Specific examples of the fenders of the present invention include, for example, the following various fenders. An arch-shaped fender (including so-called inverted V-shape, lambda (λ) shape, and beta (β) shape) is formed integrally by a cross-linked rubber composition, comprising a head that constitutes a planar impact surface to which ships or other vessels dock, and a pair of support legs that hang down from the head while expanding in the front-rear direction. A so-called kappa (κ) type fender, in which a disc-shaped head and a truncated cone-shaped support leg that extends radially downward from the head are integrally formed by a crosslinked rubber composition for fenders. A so-called π-type fender comprising a head made of steel or the like, and a pair of support legs made of a crosslinked rubber composition for fenders, which hang down from the head while expanding in the front-rear direction.
[0098] At least a portion of the fender (for example, the head and support legs) may be formed from the crosslinked rubber composition for fenders of the present invention as described above, but it is preferable that at least the support legs be formed from the crosslinked rubber composition for fenders of the present invention. In particular, in the case of arch-shaped or kappa-shaped fenders, it is also preferable to integrally form the entire fender, including not only the support legs but also the head, from the crosslinked rubber composition for fenders of the present invention. [Examples]
[0099] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples, and any modifications and embodiments that do not depart from the spirit of the present invention are all included within the scope of the present invention.
[0100] The components of the formulations shown in Table 1 were kneaded using a 3L kneader and an open roll to prepare rubber compositions for fenders.
[0101] [Table 1]
[0102] The components listed in Table 1 are as follows: Natural rubber: TSR20 product Styrene-butadiene rubber: SBR1502 (non-oil type) manufactured by JSR Corporation. Carbon Black 1: Seast 3 (HAF) manufactured by Tokai Carbon Co., Ltd. (Nitrogen adsorption specific surface area: 79 m²) 2 / g) Carbon Black 2: Seast V (GPF, Nitrogen Adsorption Specific Surface Area: 27m²) manufactured by Tokai Carbon Co., Ltd. 2 / g) Sulfur: 5% oil-treated powdered sulfur manufactured by Tsurumi Chemical Industries Co., Ltd. Crosslinking accelerator: Sancella NS-G (sulfenamide type) manufactured by Sanshin Chemical Industry Co., Ltd. 1,6-Bis(N,N-Dibenzylthiocarbamoyldithio)hexane: Vulcuren manufactured by LANXESS Crosslinking retarder: Retarder CTP (N-(cyclohexylthio)phthalimide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Zinc oxide: Two types of zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. Stearic acid: Camellia oil manufactured by NOF Corporation Plasticizer: Diana Process Oil NH-70S manufactured by Idemitsu Kosan Co., Ltd. Anti-aging agent: Nocrack 6C (aromatic secondary amine-based anti-aging agent) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: Sunnock manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0103] [Evaluation Method] <Measurement of physical properties of uncrosslinked rubber> (Degree of vulcanization test) Using a rubber composition for fenders, measurements were performed under the following conditions in accordance with the Japanese Industrial Standard JIS K6300-2:2001 "Unvulcanized rubber - Physical properties - Part 2: Method for determining vulcanization properties using a vibrating vulcanization tester". Testing machine: Curlastometer (registered trademark) Type 7 Test temperature: 140℃ Exam duration: 120 minutes From the obtained data (vulcanization time - torque), the vulcanization induction time tc(10) (vulcanization start point), the 90% vulcanization time tc(90) (optimal vulcanization point), and the crosslinking rate index Δtc(80) (=tc(90)-tc(10)) were determined in accordance with the Japanese Industrial Standard JIS K6300-2:2001. The difference between these values and the values for the standard fender No. 6 was also calculated.
[0104] <Measurement of physical properties of cross-linked rubber> (Hardness measurement test) A 2mm thick crosslinked rubber sheet was prepared by press-crosslinking a fender rubber composition at 140°C for 60 minutes. Three of these crosslinked rubber sheets were stacked to form a test specimen for hardness measurement, and the Type A durometer hardness was measured according to the measurement method specified in Japanese Industrial Standard JIS K6253-3:2012 "Vulcanized rubber and thermoplastic rubber - Method for determining hardness - Part 3: Durometer hardness". The measurement temperature was the standard test temperature (23°C).
[0105] (Tensile test) A 2 mm thick crosslinked rubber sheet was prepared by press-crosslinking a fender rubber composition at 140°C for 60 minutes. Next, the crosslinked rubber sheet was punched out to prepare dumbbell-shaped test specimens of type 3 as specified in Japanese Industrial Standard JIS K6251:2017 "Vulcanized rubber and thermoplastic rubber - Method for determining tensile properties". Tensile tests were then performed on the prepared test specimens as specified in the same standard to determine the tensile strength TS (MPa) and elongation at break Eb (%). The measurement temperature was the standard test temperature (23°C). Tensile strength (TS) was evaluated as follows: less than 16 MPa was marked "×", 16 MPa or more but less than 20 MPa was marked "○", and 20 MPa or more was marked "◎". Similarly, elongation at break (Eb) was evaluated as follows: less than 350% was marked "×", 350% or more but less than 400% was marked "○", and 400% or more was marked "◎".
[0106] (Tear test) A 2mm thick crosslinked rubber sheet was prepared by press-crosslinking a fender rubber composition at 140°C for 60 minutes. Next, the crosslinked rubber sheet was punched out to prepare crescent-shaped test specimens as specified in Japanese Industrial Standard JIS K6252:2015 "Vulcanized rubber and thermoplastic rubber - Method for determining tear strength - Part 1: Method using trouser-shaped, angle-shaped and crescent-shaped test specimens". The tear strength (N / mm) was then determined by performing a tear test on the prepared test specimens as specified in the same standard. The measurement temperature was the standard test temperature (23°C). Tear strength was evaluated as follows: less than 70 N / mm was marked "×", 70 N / mm or more but less than 90 N / mm was marked "○", and 90 N / mm or more was marked "◎".
[0107] (Compression test) A miniature-sized fender specimen 1 of the lambda type, having the end face shape shown in Figure 1, was fabricated using a rubber composition for fenders. Specifically, a head 3 constituting a planar impact surface 2, a pair of support legs 4 hanging down from the head 3 while expanding in the front-rear direction, and mounting flanges 5 connected to the lower ends of the support legs 4 and protruding outward were integrally formed using the rubber composition for fenders, and the miniature-sized fender specimen 1 was fabricated by press-crosslinking at 140°C for 120 minutes. The dimensions of each part were as follows: the width W1 of the head 3 was 65 mm, the height H was 100 mm, the width W2 between the tips of the flanges 5 was 180 mm, and the total length was 200 mm. The fabricated fender reduction test specimens were subjected to compression testing using a compression testing machine. The maximum compression amount was 52.5% of the height H, and the specimens were compressed three times at a speed of 15 mm / min in the vertical direction under standard test temperature (23°C) with a 3-minute interval between tests. The average value of the reaction force corresponding to the compression ratio during the second and third compression tests was calculated. The compression ratio-reaction force characteristics were then determined by plotting the compression ratio (%) on the horizontal axis and the reaction force (KN) on the vertical axis. The maximum value of the reaction force (maximum reaction force) was evaluated as "○" if it was greater than the standard fender No. 6, and "×" if it was smaller.
[0108] Table 1 shows the composition of the rubber composition for fenders, as well as the evaluation results for the rubber composition for fenders and its crosslinked products (crosslinked rubber sheets, fenders).
[0109] Fenders No. 6 to 8 consist of crosslinked rubber compositions containing only a crosslinking accelerator, without the addition of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane. The rubber composition for fender No. 6 is considered the standard composition. The rubber composition for fender No. 7 has a reduced amount of crosslinking accelerator compared to the standard composition. Compared to the rubber composition for fender No. 6, the vulcanization induction time tc(10) is slightly longer, but the maximum reaction force of the fender is significantly reduced. The rubber composition for fender No. 8 has an additional crosslinking retarder added to the standard composition. Compared to the rubber composition for fender No. 6, the vulcanization induction time tc(10) is longer, but the maximum reaction force of the fender is reduced.
[0110] On the other hand, fenders No. 1 to 5 consist of a crosslinked rubber composition containing both 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and a crosslinking accelerator, with the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane being between 0.1 parts by mass and less than 1.0 part by mass per 100 parts by mass of the base rubber. Compared to the standard fender No. 6, these fenders No. 1 to 5 showed a longer vulcanization induction time tc(10) of the rubber composition, and the maximum reaction force of the resulting fenders did not decrease. Of these, fenders No. 1 and 2 had a crosslinking accelerator content less than or equal to the content of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane. Compared to the standard fender No. 6, the vulcanization induction time tc(10) of the rubber composition was longer, and the maximum reaction force of the fender did not decrease, while the elongation at break was greater. Fenders No. 3 to 5 had a crosslinking accelerator content greater than the content of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane. Compared to the standard fender No. 6, the vulcanization induction time tc(10) of the rubber composition was longer, the 90% vulcanization time tc(90) did not change significantly, and Δtc(80), which is an indicator of crosslinking rate, was shorter. Furthermore, the maximum reaction force of the obtained fenders did not decrease. In particular, fenders No. 3 and 4, in which the amount of crosslinking accelerator is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.5 parts by mass or less, show that the vulcanization induction time tc(10) of the rubber composition is longer than that of the standard fender No. 6, the 90% vulcanization time tc(90) does not change significantly, the Δtc(80) which is an indicator of the crosslinking rate is shorter, and the tear strength is significantly improved without a decrease in the maximum reaction force of the resulting fenders.
[0111] The rubber composition for fenders of the present invention has a long vulcanization induction time tc(10), improved processing stability, and no decrease in the reaction force of the fender. Therefore, an improvement in product (fender) quality can be expected. Furthermore, because the rubber composition for fenders of the present invention has a long vulcanization induction time tc(10), the crosslinking temperature can be increased by adjusting the rubber compound, or the mold temperature and rubber temperature during rubber filling can be increased, which can be expected to shorten the crosslinking time. Moreover, compared to the rubber composition for fenders of the present invention described in Patent Document 4 above, which contains 1.0 part by mass or more of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, the rubber composition for fenders of the present invention has a reduced amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, so it can be expected that fenders can be manufactured at a lower cost. [Explanation of symbols]
[0112] 1: Fender reduction test specimen, 2: Impact surface, 3: Head, 4: Support leg, 5: Flange
[0113] A preferred embodiment (1) of the present invention is a rubber composition for fenders that contains a base rubber including natural rubber, carbon black, a crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and a crosslinking accelerator, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.1 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
[0114] A preferred embodiment (2) of the present invention is a rubber composition for fenders according to embodiment (1), wherein the amount of the crosslinking accelerator is less than or equal to the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
[0115] A preferred embodiment (3) of the present invention is a rubber composition for fenders according to embodiment (1) or (2), wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane blended is 0.5 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
[0116] A preferred embodiment (4) of the present invention is a rubber composition for fenders according to any one of embodiments (1) to (3), wherein the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and less than 2.0 parts by mass per 100 parts by mass of the base rubber.
[0117] A preferred embodiment (5) of the present invention is a rubber composition for fenders in embodiment (1) in which the amount of the crosslinking accelerator is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
[0118] A preferred embodiment (6) of the present invention is a rubber composition for fenders according to embodiment (1) or (5), wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane added is 0.1 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of base rubber.
[0119] A preferred embodiment (7) of the present invention is a rubber composition for fenders of any one of embodiments (1), (5), or (6), wherein the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.6 parts by mass or more and 3.5 parts by mass or less per 100 parts by mass of the base rubber.
[0120] A preferred embodiment (8) of the present invention is a rubber composition for fenders of any one of embodiments (1) to (7), wherein the natural rubber content in the base rubber is 50% by mass or more and 95% by mass or less.
[0121] A preferred embodiment (9) of the present invention is a rubber composition for fenders of any one of embodiments (1) to (8), wherein the base rubber further comprises styrene-butadiene rubber.
[0122] A preferred embodiment (10) of the present invention is a rubber composition for fenders of any one of embodiments (1) to (9), wherein the amount of carbon black added is 60 parts by mass or more and 90 parts by mass or less per 100 parts by mass of base rubber.
[0123] A preferred embodiment (11) of the present invention is a fender having a head portion having a contact surface for docking with ships and the like, and a support leg portion that supports the head portion, wherein at least the support leg portion contains a crosslinked material of any one of the fender rubber compositions of embodiments (1) to (10).
Claims
1. A rubber composition for fenders, characterized in that it contains a base rubber including natural rubber, carbon black, a crosslinking agent, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and a crosslinking accelerator, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.1 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
2. The rubber composition for fenders according to claim 1, wherein the amount of the crosslinking accelerator is less than or equal to the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
3. The rubber composition for fenders according to claim 2, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane added is 0.5 parts by mass or more and less than 1.0 part by mass per 100 parts by mass of the base rubber.
4. The rubber composition for fenders according to claim 3, wherein the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and less than 2.0 parts by mass per 100 parts by mass of the base rubber.
5. The rubber composition for fenders according to claim 1, wherein the amount of the crosslinking accelerator is greater than the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane.
6. The rubber composition for fenders according to claim 5, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane added is 0.1 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the base rubber.
7. The rubber composition for fenders according to claim 6, wherein the total amount of the crosslinking accelerator and 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 0.6 parts by mass or more and 3.5 parts by mass or less per 100 parts by mass of the base rubber.
8. The rubber composition for fenders according to claim 1, wherein the content of natural rubber in the base rubber is 50% by mass or more and 95% by mass or less.
9. The rubber composition for fenders according to claim 1, wherein the base rubber further comprises styrene-butadiene rubber.
10. The rubber composition for fenders according to claim 1, wherein the amount of carbon black added is 60 parts by mass or more and 90 parts by mass or less per 100 parts by mass of base rubber.
11. A fender having a head portion having a contact surface for docking with ships and the like, and a support leg portion that supports the head portion, wherein at least the support leg portion contains a crosslinked material of the rubber composition for fenders described in any one of claims 1 to 10.
Citation Information
Patent Citations
Rubber composition for fender and fender therewith
JP2022025537A
Rubber composition for fender and fender using therewith
JP2022076692A
Rubber composition for fender and fender using the same
JP2022145069A
Rubber composition for fenders and fender using the same
JP2025020954A